PENERAPAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X MAN 1 PEKANBARU - Aulea Dymas Yolanda Dymas Yolanda; Jimmi Copriady Copriady; Sri Haryati Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The research on application of active learning strategy to Active Knowledge Sharing has been done to improve student achievement on the subject of Atomic Structure in class X IPA MAN 1 Pekanbaru on September until October 2014. Form of the research is experimental research with pretest-postest design. The sample consisted of two classes, class X IPA 2 as the experiment and class X IPA 1 as control class which randomly selected after had tested normality and homogeneity. Experimental class is a class that implemented Active Knowledge Sharing strategy. Data analysis technique used the t-test. Based on the result of the final data processing t-test formula obtained tcount>ttable (2,94>1,67) means the application of active knowledge sharing strategy can improve student achievement on the subject of atomic structure in class X MAN 1 Pekanbaru. The improvement of student’s achievement in experiment class was supported by N-Gain score 0,76 that included in high category. Keywords : Active Knowledge Sharing, Learning achievement, Atomic Structure